Epidemiology of two large measles virus outbreaks in Catalonia. What a difference the month of administration of the first dose of vaccine makes (2013)
Measles cases in the European Region have been increasing in the last decade; this illustrates the challenge of what we are now encountering in the form of pediatric preventable diseases. In Catalonia, autochthonous measles was declared eliminated in the year 2000 as the result of high measles-mumps-rubella vaccine (MMR) coverage for first and second dose (15 mo and 4 y) since the mid-1990s. From then on, sporadic imported cases and small outbreaks appeared, until in 2006–2007 a large measles outbreak affecting mostly unvaccinated toddlers hit the Barcelona Health Region. Consequently, in January 2008, first dose administration of MMR was lowered from 15 to 12 mo of age. A new honeymoon period went by until the end of 2010, when several importations of cases triggered new sustained transmission of different wild measles virus genotypes, but this time striking young adults. The aim of this study is to show the effect of a change in MMR vaccination schedule policy, and the difference in age incidence and hospitalization rates of affected individuals between both outbreaks. Epidemiologic data were obtained by case interviews and review of medical records. Samples for virological confirmation and genotyping of cases were collected as established in the Measles Elimination plan guidelines. Incidence rate (IR), rate ratio (RR) and their 95% CI and hospitalization rate (HR) by age group were determined. Statistic z was used for comparing proportions. Total number of confirmed cases was 305 in the 2010 outbreak and 381 in the 2006–2007 outbreak; mean age 20 y (SD 14.8 y; 3 mo to 51 y) vs. 15 mo (SD 13.1 y; 1 mo to 50 y). Highest proportion of cases was set in ≥ 25 y (47%) vs. 24.2% in 2006 (p < 0.001). Differences in IR for ≤ 15 mo (49/100,000 vs. 278.2/100,000; RR: 3,9; 95%CI 2,9–5.4) and in overall HR 29.8% vs. 15.7% were all statistically significant (p < 0.001). The change of the month of age for the administration of the first MMR dose proved successful to protect infants. Yet, given the current epidemiological situation, continued awareness and efforts to reach young adult population, especially those at high risk of infection and transmission such as healthcare workers and travelers, are needed to stop the spread of the virus when importations occur.